Optimizing Raw Material Inventory Control with Continuous and Periodic Review - Farel, Febrian Muhammad; Aryanny, Enny (Newinera Publisher, 2024)
PT XYZ is a plywood processing firm confronted with issues related to raw material inventory management since the demands for such materials are probabilistic in nature and the orders could not be ordered based on the needs of the company’s production line. This often leads to problems such as overstock and stockout hence increasing the overall cost of inventory. This research is going to find ways on supply management of sengon wood to be used in PT XYZ by identifying the difference between the existing inventory management technique that the company is using, the continuous review (Q) back order method and the periodic review (P) back order method to retail total inventory costs. From the findings, it is established that employing continuous review back order method (Q) bring in total stocks cost to the tune of IDR 28,829,527,844 which is cheaper than the total costs obtained under current firms method resulting to the tune of IDR 32,502,564,700 in the process giving an 11.3% cost savings. Moreover, based on the estimated demand of sengon wood from May 2024 to April 2025 as 42,109 m³, another improvement called the continuous review method helped to optimize the use of inventory. This research validates the effectiveness of such inventory tracking systems as the continuous inventory monitoring system particularly for businesses that operate in volatile markets hence the implication of great savings when compared to the conventional systems of inventory control.